Jiří Jiráček. Issue 37 (2nd October 2018) - Unknown
Abstract: "The Jiráček group is interested in all aspects of insulin and insulin‐like growth factors 1 and 2 (IGF‐1 and ‐2) physiology." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800601 andhttps://doi.org/10.1002/ejoc.201800606 . Abstract : "The Jiráček group is interested in all aspects of insulin and insulin‐like growth factors 1 and 2 (IGF‐1 and ‐2) physiology." Find out more about this author's research athttps://doi.org/10.1002/ejoc.201800601 andhttps://doi.org/10.1002/ejoc.201800606 .